DETERMINANTS OF JOB SATISFACTION AMONG FOR-PROFIT NURSING HOME CARE WORKERS IN KLANG VALLEY: THE MEDIATING ROLE OF ORGANIZATIONAL SUPPORT AND WORK ENGAGEMENT - Azmi, Adlina; Hasbollah, Hasif Rafidee; Yasin, Nurul Hafizah Mohd; Adnan, Adni Halianie (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study investigates the determinants of job satisfaction, specifically job demands and job resources, among care workers in for-profit nursing homes in Klang Valley, Malaysia. Particular attention is given to the mediating roles of organizational support and work engagement. Grounded in the Job Demands–Resources (JD-R) model, this study examines the impact of job demands and job resources on job satisfaction. A quantitative, cross-sectional research design was adopted, utilizing a structured questionnaire administered to 150 care workers selected through two-stage cluster random sampling. The study measured five key constructs: job demands, job resources, organizational support, work engagement, and job satisfaction. Findings indicate that excessive job demands negatively impact job satisfaction, while sufficient job resources and strong organizational support enhance work engagement and job satisfaction. Structural equation modeling revealed that both organizational support and work engagement mediate the relationship between job demands, job resources, and job satisfaction. These findings offer practical implications for policymakers and administrators of for-profit nursing homes by underscoring the importance of fostering a supportive work environment and ensuring adequate resources. The study contributes to the theoretical development of the JD-R model within the Malaysian context. It aligns with the Sustainable Development Goals (SDGs) by promoting decent work conditions in eldercare services.